Assessing milk products quality, safety, and influencing factors along the dairy value chain in eastern Democratic Republic of the Congo - Bacigale, S.B.; Ayagirwe, R.; Mutwedu, V.B.; Mugumaarhahama, Y.; Mugisho, J.Z.; Nziku, Z.; Fofana, M.; Udomkun, Patchimaporn; Mignouna, J. (Frontiers Media, 2023)
Dairying is one of the new promising economic sectors in eastern Democratic Republic of Congo (DRC), but still not explored enough to ensure consumers' safety. This study aimed to assess the health risks and nutritional profile of milk products along the value chain in South-Kivu and Tanganyika provinces. A total of 288 milk actors, including 160 producers, 35 collectors and 93 vendors, were concerned for interview and milk samples collection. A total of 302 milk samples (159 raw, 44 pasteurized, 76 fermented and 19 white cheese so-called “Mashanza”) were collected for physicochemical [pH, fat, non-fat dry matter (NFDM), lactose, protein, freezing point, density] and microbiological (total Aerobic Mesophilic Flora, Escherichia coli, Total Coliforms, Fecal Coliforms, Salmonella and Staphylococci) analyses. Results revealed that the physicochemical characteristics of the milk mostly varied according to the type of milk and the regions. The pasteurized milk from Tanganyika presented the best physicochemical parameters [crude protein (CP) = 4.36%, Fat = 4.06%, NFDM = 12%, lactose = 5.4%, density = 1.02 and pH = 6.59] compared to other types of milk. For microbiology, no E. coli was recorded but Salmonella and Staphylococci were found in all the milk types with the values not exceeding 3 × 104 CFU ml−1 and 3 × 103 CFU ml−1, respectively. This implies a long-term consumers' health issue if appropriate measures are not taken by milk actors along the value chain. The microbiological quality was influenced by the ecologies of production axis (representing the production zones) and by handling methods and infrastructures used by the actors involved along the value chain. Factors related to animal husbandry, milking method, milk processing and packaging had no significant effect on the physicochemical parameters under study. These results indicated that health risks for milk consumers are accrued by production practices and handling by milk actors due to shortage of required skills and appropriate equipment along the milk value chain. Observance of hazard analysis critical control point (HACCP) measures is carefully required along the milk value chain nodes to improve the quality of milk produced and sold and thus reduce the risks among consumers in South-Kivu and Tanganyika provinces.